Microneedle Array Patch Made of Kangfuxin/Chitosan/Fucoidan Complex Enables Full-Thickness Wound Healing - Yu, Xixi; Wang, Caixia; Wang, Yuanfei; Li, Longhao; Gao, Xiang; Zhu, Tingting; An, Pugen; Meng, Zhaojian; Wang, Wanchun; Wu, Tong; Hao, Yuanping (Frontiers in Chemistry, 2022)
Skin wound caused by external injury is usually difficult to be cured by conventional topical administration because of its poor drug penetration across the stratum corneum. It has been recognized that stratum corneum is the main obstacle for transdermal drug delivery. To address this issue, microneedles (MNs) have been developed to penetrate the stratum corneum of skin and then form micron-sized pores between the epidermis and the dermis layers. As such, biomacromolecule drugs and/or insoluble drug molecules can be allowed for effective transdermal penetration. A multifunctional microneedle-array patch capable of avoiding wound infection as well as promoting tissue remolding is of great value for wound healing. Among others, marine polysaccharides have drawn much attention for multifarious biomedical applications due to their excellent (bio)physicochemical properties. Herein, we develop a microneedle-array patch using a blend of Chitosan (CS), Fucoidan (FD), and Kangfuxin (KFX), named KCFMN, for accelerating full-thickness wound healing. The Chinese medicine named Kangfuxin extracted from Periplaneta americana (PA) has effective bio-functions in promoting wound healing. The macro/microscopic morphologies and (bio)physicochemical properties of such composite microneedles were also investigated. We showed that the KCFMN patch displayed not only noticeable anti-bacterial properties but also good cytocompatibility and histocompatibility. In particular, the KCFMN patch significantly accelerated the wound healing process in a full-thickness skin wound model in rats. Thus, this versatile KCFMN patch has great promise for the application of full-thickness wound healing.